2015
DOI: 10.1177/1468794115619001
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on co-investigation through peer research with young people and older people in sub-Saharan Africa

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 17 publications
0
41
0
1
Order By: Relevance
“…Throughout the study, we worked not only with research assistants from in-country collaborating institutions but also with a small group of 'peer researchers': young people we initially trained in 2006/2007 as schoolchildren (approximately 11-19 years) and who played a valuable role in identifying important questions for further investigation by the academic team Porter, 2016;Porter et al, 2010;Robson, Porter, Hampshire, & Bourdillon, 2009). They conducted interviews with their peers early in the research process and subsequently according to their availability.…”
Section: Methodsmentioning
confidence: 99%
“…Throughout the study, we worked not only with research assistants from in-country collaborating institutions but also with a small group of 'peer researchers': young people we initially trained in 2006/2007 as schoolchildren (approximately 11-19 years) and who played a valuable role in identifying important questions for further investigation by the academic team Porter, 2016;Porter et al, 2010;Robson, Porter, Hampshire, & Bourdillon, 2009). They conducted interviews with their peers early in the research process and subsequently according to their availability.…”
Section: Methodsmentioning
confidence: 99%
“…Our method has been somewhat unusual from the start, in that we commenced by training seventy young people (schoolchildren aged eleven to nineteen years) in 2006 as co-researchers. They helped establish key questions for further substantial qualitative and quantitative research by the academic research teams (Porter et al 2010; Porter 2016a). Some of those ‘young researchers’ have continued to work with us in the phones project, joining the academic teams and contributing to both qualitative and survey components.…”
Section: ‘When the Far Away Becomes Nearby’6mentioning
confidence: 99%
“…In LMICs, what appears to have been the first participatory research with children and young people (aged 9-18 years) on transport issues started in 2004 with pilots in India, Ghana and South Africa, followed by a major study across 24 sites in Ghana, South Africa and Malawi. This incorporated in-depth qualitative research taking an ethnographic approach plus an extensive survey (N = 3000) [11][12][13][14][15][16]. The research went beyond adults simply asking young people for their views on transport issues.…”
Section: Youth Voicementioning
confidence: 99%
“…There is also ample evidence of actual harassment of women globally and on a daily basis, with recent statistics suggesting, for instance, that over 70% of women in Karachi had experienced harassment on public transport and 90% in Sri Lanka, while 89% of women in Santiago had either seen or experienced it themselves [83] (pp. [15][16]. Participants in a Chennai research study reported 14 years as the mean age at which they first encountered harassment in travel contexts; harassment was worst at night [118].…”
Section: Travel Safety and Securitymentioning
confidence: 99%